Decline in transmission of schistosomiasis mansoni in Oman. Issue 1 (December 2016) - Al Abaidani, Idris; Al-Abri, Seif; Shaban, Mahmoud; Ghugey, Satish; Al Kathery, Salem; Al-Mashikhi, Khalid; Garba, Amadou; Gabrielli, Albis
Abstract Background Intestinal schistosomiasis due toSchistosoma mansoni was first reported in Oman in 1979. We describe the trend in parasitological and serological prevalence of human infection withS. mansoni in the endemic area over the period 1982–2014, and the compliance of data generated by the national monitoring and evaluation system with schistosomiasis elimination criteria set by the Ministry of Health of Oman. Methods Parasitological and serological assessments were carried out on population (mainly children) living in the area at risk for schistosomiasis in Dhofar, the country's only endemic Governorate, for a period of over 30 years. Kato-Katz thick smear and Indirect Haemagglutination Assay were the techniques employed. Results Data indicate a progressive decline in prevalence ofS. mansoni throughout the 1980s and the 1990s, a recrudescence in the early 2000s, and a more marked decrease following the implementation of six rounds of mass treatment with praziquantel from 2007 to 2013. Latest parasitological prevalence (2011) was 0%, while latest serological prevalence (2014) was 0.11%. Conclusion Transmission of schistosomiasis has reached very low levels in Oman. Elimination criteria established by the Ministry of Health of Oman (parasitological prevalence ≤ 1% and serological prevalence ≤ 5%) have been met since 2008. Further investigations are required to assess whether interruption of transmission has been achieved in some or all foci, in view of the establishment of a formal verification process under the auspices of WHO.